2008
DOI: 10.1093/annhyg/men075
|View full text |Cite
|
Sign up to set email alerts
|

Dose–Response Relationship Between Exposure to Hand-arm Vibration and Health Effects among Metalworkers

Abstract: There seems to be a dose-response relationship between the cumulative lifetime vibration dose of the HAV and finger blanching, sensorineural symptoms, symptoms of CTS and musculoskeletal symptoms of upper limbs and neck in the group of metalworkers of the study. The risk for neurosensory symptoms was the most significantly related to exposure to HAV and also to impulse vibration. Further studies are needed to confirm the present results also in other occupational groups taking into account the possible synergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…The present findings, which suggest that a doseresponse relationship exists, match the results of similar previous longitudinal studies showing evidence for a dose-response relationship between HAV exposure and neurological (sensorineural) impairment of the hand (4,20,21). However, this relationship has been unclear and has not yet been fully established (3).…”
Section: Edlund Et Alsupporting
confidence: 89%
See 2 more Smart Citations
“…The present findings, which suggest that a doseresponse relationship exists, match the results of similar previous longitudinal studies showing evidence for a dose-response relationship between HAV exposure and neurological (sensorineural) impairment of the hand (4,20,21). However, this relationship has been unclear and has not yet been fully established (3).…”
Section: Edlund Et Alsupporting
confidence: 89%
“…The neurological symptoms of HAVS and CTS are very alike and often impossible to tell apart (4). Though it may be somewhat unspecific, it is important to investigate the impact of HAV on neurological symptoms as it appears that sensorineural symptoms or injuries are more resistant to improvement than are vascular disorders after cessation of exposure to HAV (24,25).…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased prevalence or excess risk for neurosensory disturbances, CTS and/or abnormal sensory testing have been reported in crosssectional studies of HTV-exposed workers carried out in several countries (19)(20)(21). Only few studies have investigated prospectively the occurrence of neurosensory disorders in HTV-exposed workers.…”
Section: Exposure-response Relationship For Vibration-induced Sensorymentioning
confidence: 99%
“…Exposure–response relationships between vibration exposure and the vascular (Griffin et al 2003; Sauni et al 2009) and neurological (Edlund et al 2014; Sauni et al 2009) components of HAVS have been reported. The factors that may affect the risk of developing HAVS symptoms are the tools’ acceleration levels, the duration of exposure, the grip force required, the structure of the work surface, the working posture, the climatic conditions and individual susceptibility (Burström et al 2006; Griffin 1997; Ye et al 2015).…”
Section: Introductionmentioning
confidence: 99%